STRATEGI PELATIHAN KERJA DALAM MENDUKUNG LULUSAN YANG SIAP KERJA - Didin Hikmah Perkasa; Nur Vitriani; Lingga Yuliana; Ahmad Azmy (LPPM Universitas Bina Bangsa, 2024)
This article aims to discuss how to design a career strategy in the Company through job training for students who have just graduated at SMKN 16 Jakarta. Vocational students are included in the category of teenagers who in fact do not have good career maturity. Meanwhile, education in SMK is directed at the development of company/industry-based education, so efforts need to be made to improve, Improvement efforts are not enough only to be carried out by vocational teachers but also require other teachers including BK teachers. One of the things that can be done is job training and competency improvement by attending various job trainings and having competency certificates by related institutions. In addition, to support graduates who absorb work, the school must also prepare strategies so that graduates can be accepted for work by holding job fairs, education and entrepreneurship which are routinely carried out every year. Service strategies that can be provided include basic services in the form of career information media, then also need assessment of students' interest talents, consulting services and individual counseling services. Thus, it is expected that students can increase career maturity, both in identifying potential, analyzing career opportunities, and even in deciding the right career choice